2021
DOI: 10.1186/s13046-021-02103-5
|View full text |Cite|
|
Sign up to set email alerts
|

PFKFB4 is overexpressed in clear-cell renal cell carcinoma promoting pentose phosphate pathway that mediates Sunitinib resistance

Abstract: Background Kinases play critical role in clear-cell renal cell carcinoma (ccRCC). We aim to exploit novel kinase that is both protumorigenic and drugable in ccRCC. Methods Reproduction of public datasets with validation using microarray was performed to identify candidate gene. Functionality was studied using multi-omics with validation in vitro and in vivo. Results 6-Phosphofructo-2-Kinase/Fructose-2,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 37 publications
(35 reference statements)
0
30
0
Order By: Relevance
“…Although the great majority of the studies were focused on the inhibition of PFKFB3, there is record of at least one promising PFKFB4 inhibitor, 5-(n-(8-methoxy-4-quinolyl)amino)pentyl nitrate (5MPN) (Figure 4), that demonstrated an anti-proliferative effect of cancer cells both in vitro as in vivo [51]; 5MPN is a PFKFB4 specific inhibitor that binds competitively to its F6P binding site, suppressing kinase activity and consequently reducing the intracellular concentration of F-2,6-BP [51]. Recently, 5MPN was tested in combination therapy with Sunitinib, a receptor tyrosine kinase inhibitor used as a chemotherapeutic agent, showing promising results [52].…”
Section: Inhibitorsmentioning
confidence: 99%
“…Although the great majority of the studies were focused on the inhibition of PFKFB3, there is record of at least one promising PFKFB4 inhibitor, 5-(n-(8-methoxy-4-quinolyl)amino)pentyl nitrate (5MPN) (Figure 4), that demonstrated an anti-proliferative effect of cancer cells both in vitro as in vivo [51]; 5MPN is a PFKFB4 specific inhibitor that binds competitively to its F6P binding site, suppressing kinase activity and consequently reducing the intracellular concentration of F-2,6-BP [51]. Recently, 5MPN was tested in combination therapy with Sunitinib, a receptor tyrosine kinase inhibitor used as a chemotherapeutic agent, showing promising results [52].…”
Section: Inhibitorsmentioning
confidence: 99%
“…Eight genes (PFKFB4, MSC-AS1, SPESP1, CTSV, CHST1, TMCO3, BMP6, and PAGE2) were incorporated into the final prognostic signature. It is reported that 6-phosphofructo-2-kinase/fructose-2,6-bisphosphatase 4 (PFKFB4) is a metabolic enzyme that mediates the proliferation, progression, and drug resistance of a variety of tumors through glucose metabolism ( Dasgupta et al, 2018 ; Gao et al, 2018 ; Feng et al, 2021 ; Shen et al, 2021 ). Musculin antisense RNA 1 (MSC-AS1) is a lncRNA, which interacts largely with miRNAs and acts as an oncogene in several cancers ( Li et al, 2021 ; Liu et al, 2021 ; Ma et al, 2021 ; Zhao et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Warburg pathway enzyme fructose-6-phosphate 2-kinase/fructose-2,6-bisphosphatase 4 (PFKFB4) is a newly identified key factor in the regulation of transcriptional reprogramming. 7 PFKFB4 has been reported to be overexpressed in gastric, breast, thyroid, bladder, and colon cancer tissues; however, relatively little is known about the function and biological role of PFKFB4 in NSCLC.…”
Section: Introductionmentioning
confidence: 99%